Candida rugosa lipase covalently immobilized on facilely-synthesized carbon nitride nanosheets as a novel biocatalyst. Issue 26 (17th April 2018) - Li, Ya; Ruan, Zhijun; Zheng, Mingming; Deng, Qianchun; Zhang, Shan; Zheng, Chang; Tang, Hu; Huang, Fenghong; Shi, Jie
Abstract : We report a rational design and fabrication of immobilized Candida rugosa lipase based on carbon nitride nanosheets (C3 N4 -NS) as the matrix. . Abstract : The immobilization of lipase on solid supports provides a significant improvement to the stability and reusability of lipase. During immobilization, the restricted surface area and inferior separation capacity of matrix materials are crucial for obtaining high-quality immobilized lipase. Carbon nitride nanosheets (C3 N4 -NS) as a type of two-dimensional nanomaterial have attracted various attentions for their prominent 2D planar nanostructure, characteristic surface area, thermostability and biocompatibility. Herein, we report a rational design and fabrication of immobilized Candida rugosa lipase based on carbon nitride nanosheets (C3 N4 -NS) as the matrix. The synthetic C3 N4 -NS are characterized by transmission electron microscopy, Brunauer–Emmett–Teller gas sorptometry measurement, X-ray powder diffraction, Fourier transform infrared spectroscopy and thermogravimetric analysis. These results show that C3 N4 -NS possess an as-expected two-dimensional nanostructure with a large surface area of 74.374 m 2 g −1 . In addition, we chose glutaraldehyde-assisted covalent attachment to combine C3 N4 -NS and Candida rugosa lipase (CRL) via amino groups at the margins of C3 N4 -NS. The as-constructed immobilized lipase (C3 N4 -NS@CRL) exhibits satisfactory enzyme-loading (44.76 mg g −1 ), pH-flexibility, thermostability (after 180 min at 50 °C, 67% of the initial activity remained) and recyclability (after 10 runs, 72% of the initial activity remained). When compared with the free CRL, all experimental data indicate that C3 N4 -NS@CRL exhibited improved stability and enhanced practicability. To our knowledge, this is the first report of the application of carbon nitride nanosheets to enzyme immobilization.